Hydrologic Change in New Zealand During the Last Deglaciation Linked to Reorganization of the Southern Hemisphere Westerly Winds. Issue 12 (26th December 2019) - Hinojosa, Jessica L.; Moy, Christopher M.; Vandergoes, Marcus; Feakins, Sarah J.; Sessions, Alex L.
Abstract: Millennial‐scale climate anomalies punctuating the last deglaciation were expressed differently in the Northern and Southern Hemispheres. While changes in oceanic meridional overturning circulation have been invoked to explain these disparities, the nearly synchronous onset of such events requires atmospheric mediation. Yet the extent and structure of atmospheric reorganization on millennial timescales remains unclear. In particular, the role of the Southern Hemisphere westerly winds and associated storm tracks is poorly constrained, largely due to the paucity of accessible archives of wind behavior. Here we present a new paleohydrologic record from a Lake Hayes, New Zealand (45°S), sediment core from 17–9 ka. Using two independent proxies for lake hydrology (Ca/Ti in sediments and δD values of aquatic plant biomarkers), we find evidence for a wetter Antarctic Cold Reversal (14.7–13.0 ka) and a drying trend during the Younger Dryas (12.9–11.6 ka) and early Holocene (11.7 ka onward in this record). Comparisons of the Lake Hayes record with other Southern Hemisphere sites indicate coherent atmospheric shifts during the Antarctic Cold Reversal and Younger Dryas, whereby the former is wetter/cooler and the latter is drier/warmer. The wet/cool phase is associated with a northward shift and/or strengthening of the Southern Hemisphere westerly winds, whereas the drier/warmer phase indicates weaker midlatitude winds. These climatic trends are opposite to the Northern Hemisphere. There is a decoupling of climatic trends between Southern Hemisphere low‐latitude and midlatitude climates in the early Holocene, which could be explained by several mechanisms, such as the retreat of Antarctic sea ice. Plain Language Summary: In this study, we reconstruct climate in New Zealand at the end of the last glacial period. We do this by measuring "proxies" of ancient climate from 17, 000 to 9, 000 years ago stored in lake sediments from Lake Hayes, New Zealand. Our findings suggest there were 1, 000‐year swings in climate, going between wetter and drier conditions at Lake Hayes. These trends are seen in other Southern Hemisphere locations and match similar climate intervals around the world. We interpret the climate shifts to be related to north‐south movement of the Southern Hemisphere westerly winds, an important but understudied part of the global climate system. Key Points: We use a multiproxy approach to reconstruct lake balance and isotopic signature at Lake Hayes, New Zealand, during the last deglaciation We present evidence for a wetter Antarctic Cold Reversal and drier Younger Dryas and early Holocene in southern New Zealand We link these climate anomalies to migrations of the Southern Hemisphere westerly winds